Traumatic tympanic membrane perforations: an overview in tertiary care hospital - Shahid Rasool; Farooq Ahmad; Rauf Ahmad (The Egyptian Journal of Otolaryngology, 2016)
Abstract This hospital-based prospective study was conducted in the Department of Ear Nose Throat, Head and Neck Surgery, Government Medical College Srinagar, Jammu and Kashmir, for a period of 1 year from June 2013 to June 2014 with the aim of studying the aetiological factors, clinical presentation and management options for traumatic tympanic membrane perforations. A total of 50 patients with traumatic perforations of the tympanic membrane were enrolled in the study, comprising of 34 males and 16 females patients. Age of the patients ranged from 12 to 56 years, with a mean age of 32 years. The results showed that the most common mode of trauma was slaps (56%); sudden hearing loss and tinnitus were the two most common presentations (92%). Audiometry shows that the larger the tympanic membrane perforation, the larger the air–bone gap. Hearing loss was highest at the lowest frequencies and generally decreased as the frequency increased. The differences in air–bone gaps between small and large perforations were significant at all frequencies (P<0.05, Student’s t-test). Overall, 72% of patients responded to conservative management, whereas 28% needed fat myringoplasty and/or chemical cauterization.